Formulation and evaluation of curcumin coated central venous catheters in the eradication of catheter-related blood stream infections - Nissara Ahammed; Sundaramoorthi, Revathi; Venkatesh Dinnekere Puttegowda; Umashankar Chikkanna (Creative Pharma Assent, 2025)
Background: Biofilm formation on catheters after implantation, leading to the development of catheter-related bloodstream infections, is a significant concern with the usage of vascular catheters, leading to the death of hospitalized patients. The research aimed to modify the catheter surface by developing a coating technique using PU, PVP, and curcumin. Methodology: A dip coating technique with a base coat of PU and a top coat of PVP was used on 7 French triple-lumen Polyurethane CVCs with the antimicrobial agent Curcumin. Based on the concentration of polyurethane used, 5 formulations were prepared and evaluated as per ISO guidelines. Results and Discussion: Dip coating was successful in coating the catheters. All the physical parameters were within the ISO limits. The process parameters that produce uniform coating were studied. The coated catheters were radiopaque. At the end of 24 hours, all formulations displayed an initial burst release due to the top coat of PVP. Formulation E demonstrated a sustained release of 94.17% of the drug over 21 days. The amount of polyurethane included in the base coat determines how long the sustained release lasts. The formulation follows zero-order kinetics and fits the Higuchi model with quasi-Fickian release, indicating that the release is diffusion-controlled. Conclusion: The dip coating technique proved to be a successful method for developing drug-coated central venous catheters. Coating with curcumin reduces bacterial colonization, growth on the catheter surface, and biofilm formation, thereby preventing CRBSI, which in turn enhances patient outcomes and lowers healthcare expenses.